Variation in Hospital Use of Postacute Care After Surgery and the Association With Care Quality. Issue 2 (February 2016) - Sacks, Greg D.; Lawson, Elise H.; Dawes, Aaron J.; Weiss, Robert E.; Russell, Marcia M.; Brook, Robert H.; Zingmond, David S.; Ko, Clifford Y.
Abstract : Background: Little is known about hospital use of postacute care after surgery and whether it is related to measures of surgical quality. Research Design: We used data merged between a national surgery registry, Medicare inpatient claims, the Area Resource File, and the American Hospital Association Annual Survey (2005–2008). Using bivariate and multivariate analyses, we calculated hospital-level, risk-adjusted rates of postacute care use for both inpatient facilities (IF) and home health care (HHC), and examined the association of these rates with hospital quality measures, including mortality, complications, readmissions, and length of stay. Results: Of 112, 620 patients treated at 217 hospitals, 18.6% were discharged to an IF, and 19.9% were discharged with HHC. Even after adjusting for differences in patient and hospital characteristics, hospitals varied widely in their use of both IF (mean, 20.3%; range, 2.7%–39.7%) and HHC (mean, 22.3%; range, 3.1%–57.8%). A hospital's risk-adjusted postoperative mortality rate or complication rate was not significantly associated with its use of postacute care, but higher 30-day readmission rates were associated with higher use of IF (24.1% vs. 21.2%, P =0.03). Hospitals with longer average length of stay used IF less frequently (19.4% vs. 24.4%, P <0.01). Conclusions: Hospitals vary widely in their use of postacute care. Although hospital use of postacute care was not associated with risk-adjusted complication or mortality rates, hospitals with high readmission rates and shorter lengths of stay used inpatient postacute care more frequently. To reduce variations in care, better criteria are needed to identify which patients benefit most from these services.